Anatomically based simulation of hepatic perfusion in the human liver. (31st July 2019) - Ma, Renfei; Hunter, Peter; Cousins, Will; Ho, Harvey; Bartlett, Adam; Safaei, Soroush
Abstract: Liver structures of a healthy subject are digitised and segmented from computed tomography (CT) images, and hepatic perfusion is modelled in the hepatic artery and portal vein of the healthy subject with structured tree‐based outflow boundary conditions. This self‐similar structured tree is widely used in the literature, eg, blood flow simulation in larger systemic arteries and cerebral circulation, and is used in this study to model the effect of the smaller hepatic arteries and arterioles, as well as the smaller hepatic portal veins and portal venules. Physiologically reasonable results are obtained. Since the structured tree terminates at the size of the microvasculature system in liver lobules, the structured tree boundary condition will enable the proposed organ‐level model of hepatic arterial flow to be easily connected to tissue‐level models of liver lobules. Blood flow in the hepatic vein is also modelled in this subject with three‐element Windkessel model as outflow boundary conditions. The benefit of integrating the perfusion in all hepatic vascular vessels is that it helps us analyse some complicated clinical phenomenon more efficiently, eg, one possible application is to obtain the portal pressure gradient (PPG) to help examine the reliability of hepatic venous pressure gradient (HVPG) as an indirect measure of portal pressure. Moreover, since four to six generations of hepatic vessels, which are sufficient for liver classification analysis, were employed in the model, this study is setting the computational foundation of a potentially handy surgical tool. Abstract : Haemodynamics in the hepatic artery, portal vein, and hepatic vein are modelled in an integrated and anatomically based manner. The model is setting the computational foundation of a potentially handy surgical tool, and it allows obtaining the portal pressure gradient (PPG), which serves as the gold standard for examining the reliability of the hepatic venous pressure gradient (HVPG) as an indirect measure of portal pressure. The application of structured tree outflow boundary condition enables the model to be coupled with models of liver lobule in tissue level.